การแยกและการทำให้บริสุทธิ์ของกรดไฮยาลูโรนิกจากการหมักด้วยเยื่อแผ่นกรอง - อัจฉรา สุจิตวนิช (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purpose of this research was to study the purification of hyaluronic acid for futher application. Hyaluronic acid was produced by Streptococcus zooepidermicus UN-7 in a 5-liter fermentor and the product concentration was 1,995 mg/l. Culture cells in fermentation broth was treated with sodium dodecyl sulfate to remove membrane bound hyaluronic acid. The hyaluronic acid concentration was raised to 2,122 mg/l. However its molecular weight was decreased and this step may increase contamination of fermentation broth with intracellular components, therefore, this step was not used in the purifying process. Hyaluronic acid at the ratio of ethyl alcohol to culture broth of 2 : 1. The precipitate was redissolved in 0.2 M sodium chloride solution. The protein was adsorbed by activated carbon and the low molecular weight contaminants were removed by ultrafiltration using 300,000 dalton molecular weight cut off membrane. The final concentration of hyaluronic acid solution was 2,100 mg/l with molecular weight in the range of 2.1-2.3 x 106 dalton. The purity was 83.79 percent The yield was 65.24 percent of the initial hyaluronic acid content. The contaminated protein was undetectable by Lowry method. The effects of variables on the molecular weight of the prepared hyaluronic acid were studied. The physical factors were temperature and stirring speed. The chemical factors were pH and enzyme hyaluronidase. It was found that, the molecular weight decreased approximately 20 percent at temperature 50, 70 and 100 ℃ for 48, 0.5 and 0.08 hours respectively or stirring speed of 200 and 400 rpm for 4 and 0.5 hours respectively or maintain at pH 1, 3 and for 13 for 0.5, 1 and 0.25 hour respectively or in the presence of enzyme hyaluronidase only µg/ml or 0.5 unit enzyme activity/ml for 0.10 hour.